2016
DOI: 10.3389/fpls.2016.01471
|View full text |Cite
|
Sign up to set email alerts
|

The Difference of Physiological and Proteomic Changes in Maize Leaves Adaptation to Drought, Heat, and Combined Both Stresses

Abstract: At the eight-leaf stage, maize is highly sensitive to stresses such as drought, heat, and their combination, which greatly affect its yield. At present, few studies have analyzed maize response to combined drought and heat stress at the eight-leaf stage. In this study, we measured certain physical parameters of maize at the eight-leaf stage when it was exposed to drought, heat, and their combination. The results showed an increase in the content of H2O2 and malondialdehyde (MDA), and in the enzyme activities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 63 publications
3
81
0
Order By: Relevance
“…Chlorophyll fluorescence, an indicator of efficiency of electron transport during the light reaction of photosynthesis, decreased in the present study due to damage to chlorophyll and possibly proteins of reaction centres, which might impair the electron flow in leaves of stressed lentil plants, in a way similar reports in Kentucky bluegrass ( Poa pratensis L; Jiang & Huang, ), chickpea (Awasthi et al, ), and tomato (Nankishore & Farrell, ). The reduction in photosynthesis, especially in combined stressed plants, might have occurred due to decline in stomatal conductance, decreased leaf water content, damaged chlorophyll, and inhibited carbon fixation enzymes (Zhao et al, ) and is similar to findings in tomato (Nankishore & Farrell, ), chickpea (Awasthi et al, ), and barley (Jedmowski, Ashoub, Momtaz, & Brüggemann, ). The increase in stomatal conductance during heat stress is an adaptive response, which facilitates transpirational cooling of the leaves and is similar to observations in wheat (Sharma, Andersen, Ottosen, & Rosenqvist, ), whereas decrease in stomatal conductance during drought stress may be due to reduced leaf water potential (Ludlow & Muchow, ) or humidity in the atmosphere (Maroco, Pereira, & Chaves, ).…”
Section: Discussionsupporting
confidence: 76%
“…Chlorophyll fluorescence, an indicator of efficiency of electron transport during the light reaction of photosynthesis, decreased in the present study due to damage to chlorophyll and possibly proteins of reaction centres, which might impair the electron flow in leaves of stressed lentil plants, in a way similar reports in Kentucky bluegrass ( Poa pratensis L; Jiang & Huang, ), chickpea (Awasthi et al, ), and tomato (Nankishore & Farrell, ). The reduction in photosynthesis, especially in combined stressed plants, might have occurred due to decline in stomatal conductance, decreased leaf water content, damaged chlorophyll, and inhibited carbon fixation enzymes (Zhao et al, ) and is similar to findings in tomato (Nankishore & Farrell, ), chickpea (Awasthi et al, ), and barley (Jedmowski, Ashoub, Momtaz, & Brüggemann, ). The increase in stomatal conductance during heat stress is an adaptive response, which facilitates transpirational cooling of the leaves and is similar to observations in wheat (Sharma, Andersen, Ottosen, & Rosenqvist, ), whereas decrease in stomatal conductance during drought stress may be due to reduced leaf water potential (Ludlow & Muchow, ) or humidity in the atmosphere (Maroco, Pereira, & Chaves, ).…”
Section: Discussionsupporting
confidence: 76%
“…In this study, the content of proteases increased in the stressed plants of both the genotypes, which imply a higher rate of damaged/unnecessary protein degradation occurred under stress, indicating the need for sensitive and selective regulation of both protein synthesis and degradation. Similarly, Aranjuelo et al (2011) found an upregulation of one of proteasome subunits in the leaves of alfalfa upon its subjection to a low water supply, and Zhao et al (2016) observed the promotion of protein hydrolysis in maize leaves subjected to drought stress. Carbohydrate and energy metabolism-related proteins like glyceraldehyde-3-phosphate dehydrogenase (GAPDH), malate dehydrogenase 2 and NDPK1 increased in DH, but GAPDH was abundant in LY.…”
Section: Discussionmentioning
confidence: 89%
“…Stable isotope labeling by amino acids in cell culture (SILAC) is one of the in vivo labeling techniques that is applied to plants, and it makes use of metabolic reactions of sample organisms [22,23]. In vitro labeling includes techniques such as an isotope-coded affinity tag (ICAT) and an isobaric tag for relative and absolute quantitation (iTRAQ) [24,25]. The acquisition of mass signals in large-scale proteomic studies employs data-dependent acquisition (DDA) strategies where a fixed number of intact peptides (MS 1 ) are selected as precursors and subsequently analyzed as fragments by tandem mass (MS/MS) [21].…”
Section: Techniques For Detection Of Post-translational Modificatimentioning
confidence: 99%